Revenue-Spend Hypothesis: Bukti Baru Kebijakan Fiskal Pemerintah Daerah - Helda Marlin Ala; Mesri Welhelmina Nisriani Manafe; Zet Ena (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2022)
This study aims to examine the relationship between Regional Original Income and Capital Expenditure on Economic Growth based on Revenue-spend hypothesis. Understanding about causality can help local governments determine strategies and policies in exploring revenue potential and reducing the level of fiscal dependence as well as evaluating and controlling to achieve an efficient level of budget use. This study uses 60 data from 15 districts in East Nusa Tenggara Province for period 2015-2018. The test using path analysis proves the direct effect of PAD on growth but has no effect on capital expenditure and supports H0 for testing the intervening variable. Novelty in this research is to fill the theoretical and empirical gap with place according to the right theory to build a basic framework through Revenue-spend hypothesis. Furthermore, this study also determines the sample that meets the criteria required which are still limitations in previous research. Limitation in this study are the research period relatively short, not able to capture changing phenomenon in variables and also has not been able to explain the non-unidirectional relationship between income and expenditure through the Revenue-spend hypothesis. Next research continued by adding or expanding the scope of research time and location, including other variables such as inflation, time span, quality and size of institutions, level of corruption, country level, amount of barriers and types of spending and income.